2021
DOI: 10.1097/ju.0000000000001441
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of the Association between Vitamin D Status and Lower Urinary Tract Symptoms

Abstract: Purpose: Cumulative studies have shown that vitamin D may be associated with lower urinary tract symptoms but the findings have been inconsistent. The aim of this study was to systematically evaluate the relationship between vitamin D and lower urinary tract symptoms. Materials and Methods: The PubMedÒ, ScopusÒ and EmbaseÔ databases were searched for articles up to June 2020. A meta-analysis was conducted to evaluate the effects of vitamin D insufficiency or intake on lower urinary tract symptoms. A qualitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…[10][11][12] A recent systematic review and meta-analysis of observational studies and clinical trials reported that vitamin D supplementation showed "promising effects" on LUTS and UI. 13 The evidence supports a higher strength of the association of vitamin D with improved UI symptoms in women. Specifically in men aged 50 and older with enlarged prostates, one randomized clinical trial (n[119) of a vitamin D analog compared to placebo reduced urinary flow rates after 12 weeks.…”
Section: Figurementioning
confidence: 73%
“…[10][11][12] A recent systematic review and meta-analysis of observational studies and clinical trials reported that vitamin D supplementation showed "promising effects" on LUTS and UI. 13 The evidence supports a higher strength of the association of vitamin D with improved UI symptoms in women. Specifically in men aged 50 and older with enlarged prostates, one randomized clinical trial (n[119) of a vitamin D analog compared to placebo reduced urinary flow rates after 12 weeks.…”
Section: Figurementioning
confidence: 73%
“… 22 It was demonstrated that VDR agonists exhibit antiproliferative and proapoptotic effects in BPH cells. 25 These protective effects are achieved by inhibiting the inflammatory response through the COX2/PGE2 and NF-KB pathways. 26 Furthermore, a specific variant of the vitamin D receptor has been found to have a protective effect against LUTS in men.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D insufficiency, which is often seen in African Americans, has been extensively studied as an exacerbating factor for LUTS [17]. A 2021 meta-analysis of 23 studies showed that Vitamin D insufficiency was associated with a 1.37-2.06-fold increased likelihood of having LUTS [17]. African Americans are at greater risk of Vitamin D deficiency due to decreased UV absorption secondary to higher skin melanin content.…”
Section: Obesity and Metabolic Risk Factorsmentioning
confidence: 99%
“…It contains seven questions related to BPH symptoms and one question related to the patient's perceived quality of life. BPH symptom severity is proportionate to the IPSS score, which ranges from 0 to 35 and categorizes symptoms as mild (1-7), moderate (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), or severe (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The IPSS survey is widely used in Urology and the AUA also encourages its use in primary care settings.…”
Section: Screening Literacy and Community Interventionmentioning
confidence: 99%